(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The article analyzes the problem of national identity in the work of one of the most famous Romanian writers and politicians, Vasile Alecsandri. The study is focused on his poetry and plays written both before and after the unification of Moldavia with Vallachia in 1859. There a re presented his opinions about the origins of the Romanians, their unity in language and traditions and also their relationship with "the Other."